2010
DOI: 10.1111/j.1365-2842.2010.02092.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the angle of the coronoid process of the mandible and the electromyographic activity of the temporal muscle in skeletal Class I and III individuals

Abstract: The aim of the present study was to verify the relationship between the angle of the coronoid process of the mandible in the latero-lateral direction and electromyographic activity of the anterior part of the temporal muscle in skeletal Class I and III individuals. Forty-five volunteers were assessed subdivided into two groups, according to angle ANB, in Class I and III. Two radiographic examinations were performed, one lateral cephalogram to measure angle ANB and one frontal cephalogram to measure the angle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Thus, the evolutionary presence or absence of secondary cartilage on the coronoid process reflects species-specific variation in functional anatomy determined by in ovo mechanical loading (Beresford, 1981; Fang and Hall, 1997; Hall, 1979; Stutzmann and Petrovic, 1975). In taxa such as humans, rats, cats, and duck, secondary cartilage forms at the jaw adductor muscle insertion (Amorim et al, 2010, 2008; Hall, 2005; Horowitz and Shapiro, 1951; Kantomaa and Rönning, 1997; Moore, 1973, 1981; Solem et al, 2011; Soni and Malloy, 1974; Vinkka, 1982; Washburn, 1947) whereas an equivalent secondary cartilage is absent in mice, guinea pigs, chick, and quail (Anthwal et al, 2008, 2015; Boyd et al, 1967; Moss and Meehan, 1970; Rot-Nikcevic et al, 2007; Shibata et al, 2003; Solem et al, 2011). Our work implies that the reason secondary cartilage forms at this location in some species and not others is due to the way embryonic motility interacts with NCM-mediated muscle pattern to create differential forces.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the evolutionary presence or absence of secondary cartilage on the coronoid process reflects species-specific variation in functional anatomy determined by in ovo mechanical loading (Beresford, 1981; Fang and Hall, 1997; Hall, 1979; Stutzmann and Petrovic, 1975). In taxa such as humans, rats, cats, and duck, secondary cartilage forms at the jaw adductor muscle insertion (Amorim et al, 2010, 2008; Hall, 2005; Horowitz and Shapiro, 1951; Kantomaa and Rönning, 1997; Moore, 1973, 1981; Solem et al, 2011; Soni and Malloy, 1974; Vinkka, 1982; Washburn, 1947) whereas an equivalent secondary cartilage is absent in mice, guinea pigs, chick, and quail (Anthwal et al, 2008, 2015; Boyd et al, 1967; Moss and Meehan, 1970; Rot-Nikcevic et al, 2007; Shibata et al, 2003; Solem et al, 2011). Our work implies that the reason secondary cartilage forms at this location in some species and not others is due to the way embryonic motility interacts with NCM-mediated muscle pattern to create differential forces.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the prenatal period, the height of ramus of mandible increases more than LBM, and the rate of increase becomes equal towards the end (19). The relationship between mandible and TM begins in the prenatal period and continues in the postnatal period (2,4,6,7,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…TCP increase in patients with CP hyperplasia. It has also been shown that there is early contact between zygomatic arc and CP (10). It may cause trismus due to an increase in HCP or a change in CP direction (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations